Tingkat Kecemasan Berhubungan dengan Kualitas Tidur Ibu Hamil Trimester III - Bingan, Eline Charla Sabatina (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2021)
Pregnancy is a biological and psychological condition which certainly requires adaptation for women who are experiencing it. In the United States there are 40 million people experiencing anxiety disorders before childbirth. Third trimester pregnant women often feel afraid and anxious about the child who will be born later, so that pregnant women experience sleep quality disturbances. The purpose of this study was to determine the relationship between anxiety level and sleep quality of third trimester pregnant women at Ketapang Health Center. This type of quantitative research with a cross sectional approach. The population was 130 respondents in the third trimester of pregnant women at the Ketapang Health Center. The number of samples was 45 respondents using purposive sampling technique. Sleep quality variables used the PSQI (Pittsburgh Sleep Quality Index) questionnaire and the anxiety level variables used the HARS (Hamilton Rating Scale For Anxiety) questionnaire with data analysis tests using the Spearman Rho correlation test with a 95% confidence level. The results of the bivariate analysis showed that respondents who experienced mild anxiety with good sleep quality were 3 people (60%) and respondents who experienced severe anxiety with poor sleep quality were 15 people (83.3%). The correlation test between Anxiety Level and Sleep Quality for Third Trimester Pregnant Women obtained p value = 0.000, so it can be concluded that there is a relationship between anxiety levels and sleep quality for third trimester pregnant women at the Ketapang Health Center. Future research is expected to use other factors that can affect the quality of sleep of pregnant women, especially in the third trimester of pregnancy.